ORAL ADMINISTRATION OF NUTMEG ON MEMORY BOOSTING AND REGAINING IN WISTAR ALBINO RATS - Jissa, G.; Sai-Sailesh, K.; Mukadan, and J. K. (BALI MEDICAL JOURNAL, 2014)
Background: This study provides further evidence for improvement of memory by oral consumption of nutmeg. The present study was undertaken with an objective to study the effects of oral administration of nutmeg on memory boosting and regaining. Methods: Here we investigate the influence of oral intake of nutmeg on behavioral task performance by using T-maze and radial arm maze and physiological measures relative to a milk control group. Results: We have observed significant memory boosting and memory regaining effects of nutmeg when administered orally. This effect may be due to facilitation of acetylcholine activity by decreasing acetylcholinesterase activity of nutmeg. Hence we recommend further research in this area by investigating compound metabolism to optimize quantification of memory performance following nutmeg consumption.
Keywords: Memory boosting, Memory retention, Nutmeg consumption